Detection of ESBLsCTX-M Gene of E.coli Isolated from Clinical Cases in Maysan Province - Rabab Naeem Alag1, ZahidSa?doon Aziz1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The antimicrobial resistance are a worldwide increasing and important problem in health care domain. ESBLs represent a main group of ?-lactamases enzymes that mostly produced by gram-negative bacteria, and give resistance toa?- lactam antibiotics, thus the detection of these enzymes are very important for optimal care of patients. The aim of this study was to determine the antibiotic profile with the prevalence of CTX-M geneaproducingaE. coli isolatesawhich recovered from clinical cases by phenotypic and genotypic methods. A total of (291) clinical samples (urine, wound swabs, blood and seminal fluids) were included in this study. All bacterial isolates were subjected to the cultural,amicroscopical, and biochemical examinations methods, confirmed byaAPI 20E and Vitek 2 system. Where the results revealed that 105 of isolates were identified as E. coli. Antibiotic sensitivity was performed by using disk diffusion methods. Investigation of extended spectrum ?-lactamase(ESBL) production for isolates was performed using Initial screening and double disc synergy method(DDST). The results showed that most isolates showed high resistance to ß-lactam and Cephalosporins antibiotics and vast amajority of isolates were resistant to aminimum ofathree classesaof antibiotics, which indicate that identified E. coli were multidrug resistant and ESBLs producer. While all isolates were sensitive to Imipenem and Amikacin. PCR technique was performed to detect ESBLs blaCTX-M gene, the results revealed that (100%) of E.coli isolates carried this gene.